Effects of repetitive loading on cfrp plate-concrete local bond stress performance - 184729 Mohd. Nazril Md. Khair; Shukur Abu Hassan, supervisor; Fakulti Kejuruteraan Mekanikal (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2008